2019
DOI: 10.1111/jzs.12291
|View full text |Cite
|
Sign up to set email alerts
|

Does your lip stick? Evolutionary aspects of the mouth morphology of the Indo‐Pacific clinging goby of theSicyopterusgenus (Teleostei: Gobioidei: Sicydiinae) based on mitogenome phylogeny

Abstract: Sicydiinae gobies have an amphidromous life cycle. Adults grow, feed, and reproduce in rivers, while larvae have a marine dispersal phase. Larvae recruit back to rivers and settle in upstream habitats. Within the Sicydiinae subfamily, the Sicyopterus genus, one of the most diverse (24 species), is distributed in the tropical islands of the Indo‐Pacific. One of the characters used to determine Sicyopterus species is the upper lip morphology, which can be either smooth, crenulated, or with papillae, and with (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…(Keith et al 2011;Taillebois et al 2014). The genus Sicyopterus of the Sicydiinae subfamily is the genus with the highest diversity of species and is widely distributed to the Indo-Pacific tropical islands (Keith et al 2005;Keith et al 2015;Lord et al 2019). It strengthens the results of this study which found Sicyopterus as the genus with the highest diversity of Gorontalo Bay waters.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…(Keith et al 2011;Taillebois et al 2014). The genus Sicyopterus of the Sicydiinae subfamily is the genus with the highest diversity of species and is widely distributed to the Indo-Pacific tropical islands (Keith et al 2005;Keith et al 2015;Lord et al 2019). It strengthens the results of this study which found Sicyopterus as the genus with the highest diversity of Gorontalo Bay waters.…”
Section: Discussionsupporting
confidence: 76%
“…The S. parvei species are known to be Indonesian local endemic (LE) (Lord et al 2019). Its distribution in Indonesia was found in Manggarai, Flores (Tjakrawidjaja 2002); Sukamade river, East Java (Rukmana et al 2014); and Java and Bali (Dahruddin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It excludes several of the characters provided in the original genus diagnosis because, according to the current knowledge of the osteology of gobioids, they appear in many groups. These characters relate to the anteriorly elongate and posteriorly broadened parasphenoid; the toothed premaxillary and dentary; the presence of small, curved, conical oral teeth; the symplectic foramen; the opercle without spines; the bifurcated posttemporal; the presence of four radials; the presence of vertebral centra that are longer than high; the caudal skeleton with two large hypural plates (Hy), comprising Hy1+2 and Hy3+4, and a small hypural plate 5; and the presence of branched fin rays (see [ 4 – 6 , 20 , 29 , 48 , 51 , 52 , 54 56 ]). The shape of the frontal bones is also excluded, as it has been shown to differ between congeneric species [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2012) Assembly of mitochondrial genome Sicyopterus lagocephalus No Chiang et al. (2015) Phylogeny (mitogenome) Sicyopterus genus No Lord et al. (2019) Populations diversity and structure Galaxias maculatus Yes Delgado et al.…”
Section: Introductionmentioning
confidence: 99%